Redefining Masculinity in the Digital Age: Vulnerability, Emotional Expression, and AI in Spike Jonze’s Her (2023) (American Journal of Interdisciplinary Research and Innovation, 2024)
This paper explores the transformation of masculinity in Spike Jonze’s 2013 film Her, examining how the protagonist Theodore’s relationship with the artificial intelligence character Samantha challenges traditional norms of masculinity. Set in a near-future Los Angeles, the film follows Theodore (Joaquin Phoenix), a lonely man who forms a relationship with his AI operating system, Samantha (Scarlett Johansson). Their unconventional bond, characterized by emotional openness and vulnerability, underscores shifting paradigms of masculinity in an increasingly digital world. Through close analysis of Theodore’s personality, emotional struggles, and interactions with Samantha, this paper argues that the film paints a nuanced portrait of contemporary masculinity. Theodore’s willingness to be emotionally vulnerable with an AI companion reflects a departure from the conventional masculine ideal of stoicism. His dependence on Samantha for emotional support also challenges the norm of male independence and self-sufficiency. Furthermore, Samantha’s influence disrupts Theodore’s understanding of intimacy and relationships, emphasizing fluidity over rigid norms. Ultimately, Theodore’s journey suggests a redefined conceptualization of masculinity –adaptive, emotionally expressive, and receptive to meaningful connections in unexpected places. Situated at the intersection of film studies, gender studies and technology, this paper illuminates how Her insightfully portrays the complex renegotiation of masculinity in an increasingly digitized and AI-integrated world.